An atypical presentation of scrub typhus - Shetty, Vishranth N.; Rao, Gurukanth; B., Jayaprakash (International Journal of Advances in Medicine, 2022)
Scrub typhus is caused by Orientia tsutsugamushi, characterised by focal or disseminated vasculitis and perivasculitis which may involve the lungs, heart, liver, spleen and central nervous system. The clinical picture and severity of the symptoms varies widely. The neurological manifestations of scrub typhus are diverse. Meningoencephalitis is classical manifestation of scrub typhus but cerebellitis, cranial nerve palsies, plexopathy, transverse myelitis, neuroleptic malignant syndrome and Guillain-Barre syndrome are other manifestations reported in literature. The availability of literature on the neurological manifestations of scrub typhus is limited to case reports mainly. This article shows a case report of neurological manifestations of scrub typhus.